O cukierniku i o drukarzu, czyli o dwóch tradycjach praw człowieka - Śledzińska-Simon, Anna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The chapter tells a story of a baker and a printer in two analogous cases in the US and Poland concerning a religious exception from the duty to provide services offered to the public on the equal basis. Drawing upon similarities and differences in the doctrinal approach to freedom of speech, freedom to exercise religion, as well as the right to marry and the principle of non-discrimination in the US and Poland, the author questions whether there are indeed two traditions of human rights protection. She speculates that in this historical moment of cultural wars the contestation of the status quo concerning religious freedoms in the US leads towards the recognition of their special position among other constitutional rights and freedoms as it is the case in Poland.
Keywords: sexual orientation; prohibition of discrimination; First Amendment; freedom of practicing religion; freedom of speech